Dietary Magnesium Intake Modifies the Association Between Vitamin D and Systolic Blood Pressure: Results From NHANES 2007–2014 - Huang, Weichao; Ma, Xiaoman; Chen, Yue; Zheng, Jiayi; Li, Haojia; Nizhamu, Ayinigaer; Hong, Qingting; Guo, Xuguang (Frontiers in Nutrition, 2022)
Introduction Although the association between blood pressure and vitamin D has been well studied, the effects of dietary magnesium intake on this relationship are still unclear. Thus, this study aimed to determine the effects of dietary magnesium intake on the association between vitamin D and blood pressure. Methods The present study analyzed data from the continuous the National Health and Nutrition Examination Survey (NHANES) 2007–2014. We included 8,799 participants aged 20 years or older. Multivariable linear regression was performed to assess the association between vitamin D and systolic blood pressure (SBP) and diastolic blood pressure (DBP). Dietary magnesium intake was stratified by low magnesium intake (<299 mg/d) and high magnesium intake (≥299 mg/d). Effect modification by dietary magnesium intake was assessed through interaction tests between vitamin D and SBP in the multivariable linear regression. Results In this cross-sectional study, we found that vitamin D was negatively related to SBP, but not to DBP. The relationship between vitamin D and SBP was different in the low and high magnesium intake group (β: −0.25 95%Cl: −0.4 0.07 vs β: −0.32 95%Cl: −0.52 -0.12). Furthermore, magnesium intake significantly modified the negative relationship between vitamin D and SBP in most of the models. Conclusion Our research showed that magnesium and vitamin D have an interactive effect in reducing SBP, which may have great importance for clinical medication.